“EFEK MAGIS” BAHASA TERHADAP KESANTUNAN BERBAHASA DALAM PERISTIWA SIDANG PELANGGARAN LALU LINTAS DI PENGADILAN NEGERI SELONG - Herman Wijaya (Balai Bahasa Nusa Tenggara Barat, 2014)
The power of language transfers message to the interlocutors more effectively. Exploitation of the language power positively could effect to the polite communication. Thus, the key problem of this study is to explore the form of words or speeches which contain power stimulating polite usage of language. This study is aimed at analyzing the data, forms of speech containing language power effect which is used by traffic judges during the trial of traffic violators. This study applies descriptivequalitative method to describe the data taken from the traffic judge and the violators’ form of speech in the traffic violation trials. The data, in verbal form, consist of dialogues between the traffic judge and violators during the trial process. Informents of this study are the traffic judge and the violators. The data consists of forms of speech or sentences uttered by the traffic judge and the violators as well as their actons or attitudes during the trial process. The data are collected through observation techniques – in passive role – with recording technique, note taking, and audiovisual recording techniques. The data are analyzed by using interactive analysis with the following steps: data reduction, transcription of recording data, data grouping, and conclusion. Based on the data of the speech acts, it is ilustrated that the language power used by the judge to create effectsto the traffic violaters contains: questions, imperative sentences, warning, requests and prohibition. The dominant form of language power used by the judge to create communication effect towards the traffic violators is imperative form of language power. Such language power is generally the form of imperative politeness in language usage.